AN ANALYSIS ON THE GRAMATICAL ERROR OF PROCEDURE TEXT WRITEN BY THE THIRD GRADE OF SMPN 286 JAKARTA - Soraya , Kety (Journal of Industrial Engineering & Management Research, 2020)
The objective of this research is to find out the empirical evidence of the English examination test content validity made by the English lecturer for the even semester of the first grade SMPN 26 Jakarta administered at the SMPN 26 Jakarta. Having analysis of the findings of this assessment, can be conclude that omission is the type mostly found in writing procedure text followed by mis formation, mis ordering and addition. These findings indicated that every learnerâ€™s expression need article but the learnerâ€™s misform and omitted the required articles. Based on the analysis of the erroneous sentences written by the students in their composition, can be interpreted that the factor which is influences student to make grammatical error is the different grammatical system of L1 and English. As we understand, Indonesian Bahasa does not have â€œto beâ€ in construction sentences.